(3GdOQI GdfMhjI aj TQM GdBLQhejIs - (3eMeO Hf CMeO Hf jYdj GdTQja GdMSfjs; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s ((3GdWGgQ Hf GdWjH Hf eMeO GdfhGdj GdZHGTj GdeGdcj s)
(3ChdgG (B:s
(3hHYO, aGdZQV HgPG GdcJGH TQM CdaGX ebOeI GdUfgGLj GdLQhej EP gj ebOeI eHGQcI ef CLd eG Cda aj Yde GdYQHjI s
(3BNQgG (B:s
(3hdcfgG NajaI ef MjK Efge de jfhhG HgG GdGfaUGd ced GdcJGH hgh GdeSei HGdOQI GdfMhjI aj TQM GdLQhejI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJHgG GdfGSN dCMeO Hf GdLhO Hf eMeO Hf jMji Hf MehO GdTQja GdhZdjSj GdeGdcjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs